Well, what do you know? when ignorance isn't an option : dissemination of information and effective records management (2012)
Presents a research review of 3 publications: The Contribution of Records Management to Good Governance by Anastasia Dikopoulou and Athanassios Mihiotis; Board Information : Meeting the Evolving Needs of Corporate Directors by Marie-Josee Roy and Corporate Governance and; Strategic Information on the Internet : a Study of Spanish Listed Companies by Isabel-Maria Garcia Sanchez, et al.
Keywords: INFORMATION DISSEMINATION